Study of the 232Th(n,f) Cross section at NCSR ‘Demokritos’ using Micromegas Detectors - Chasapoglou, Sotirios; Tsantiri, A.; Kalamara, A.; Kokkoris, M.; Michalopoulou, V.; Stamatopoulos, A.; Vlastou, R.; Lagoyannis, A.; Eleme, Z.; Patronis, N. (HNPS Advances in Nuclear Physics, 2020)
The accurate knowledge of neutron-induced fission cross sections in actinides, is of great importance when it comes to the design of fast nuclear reactors, as well as accelerator driven systems. Specifically for the 232Th(n,f) case, the existing experimental datasets are quite discrepant in both the low and high energy MeV regions, thus leading to poor evaluations, a fact that in turn implies the need for more accurate measurements. In the present work, the total cross section of the 232Th(n,f) reaction has been measured relative to the 235U(n,f) and 238U(n,f) ones, at incident energies of 7.2, 8.4, 9.9 MeV and 14.8, 16.5, 17.8 MeV utilizing the 2H(d,n) and 3H(d,n) reactions respectively, which generally yield quasi-monoenergetic neutron beams. The experiments were performed at the 5.5 MV Tandem accelerator laboratory of N.C.S.R. “Demokritos”, using a Micromegas detector assembly and an ultra thin ThO2 target, especially prepared for fission measurements at n_ToF, CERN during its first phase of operations, using the painting technique. The masses of all actinide samples were determined via α-spectroscopy. The produced fission yields along with the results obtained from activation foils were studied in parallel, using both the NeusDesc [1] and MCNP5 [2] codes, taking into consideration competing nuclear reactions (e.g. deuteron break up), along with neutron elastic and inelastic scattering with the beam line, detector housing and experimental hall materials. Since the 232Th(n,f) reaction has a relatively low energy threshold and can thus be affected by parasitic neutrons originating from a variety of sources, the thorough characterization of the neutron flux impinging on the targets is a prerequisite for accurate cross-section measurements, especially in the absence of time-of-flight capabilities. Additional Monte-Carlo simulations were also performed coupling both GEF [3] and FLUKA [4] codes for the determination of the detection efficiency.